Does Manufacturing Sector Output Significantly Predict Economic Growth in Nigeria? - Umaru, Aminu; Egede, Yakubu; Ayuba, James (Asian Journal of Economic Modelling, 2022)
The predictive power of the manufacturing output on growth is a topical issue, especially with the outbreak of the COVID-19 pandemic and its effects on global manufacturing and economic activities. As such, this study examines how Nigeria’s manufacturing output can be observed in estimating economic growth. The ARDL model and OLS technique were employed in our assessments, and quarterly data was sourced from the CBN statistical bulletin for 2019 and the NBS annual report from 2010Q1 to 2020Q4. The study finds that manufacturing output positively and significantly affects growth in Nigeria and therefore can significantly predict further economic growth and, by extension, recession in Nigeria. It also recommends the need to improve the ease of doing business and security, adjusting interest rates for manufacturers, stabilize the exchange rate, develop infrastructure, and increase interventions in the manufacturing sector in Nigeria.